Estrategia educativa para estimular el desarrollo de la comunicación y el lenguaje en niños con trastorno del espectro autista del centro de salud el cisne II - Jones de Illescas, Ingrid (2017)
The research work presented is titled Educational strategy to stimulate the development of communication and language in children with autism spectrum disorder of El Cisne II health center. It arises from the need, from the Language Therapy service of this center, to promote the social and educational inclusion of children with ASD. The problem investigated focuses on how to develop communication and language and consider integral work from these two processes. The qualitative-quantitative methodology was applied through the application of statistical methods (Analysis-synthesis, Induction-deduction, Modeling), empirical (Observation, Interview, Survey, Test, Consultation of specialists) and athematical the percentage calculation, the determination of frequencies (absolute and relative) and the processing of the data by the inverse of the normal curve…………